2017
DOI: 10.1002/chem.201702414
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer Switching Mechanism of a Naphthalimide Derivative with its Solvatochromic Behaviour: An Experimental and Theoretical Study with In Cell Investigations

Abstract: The sole existence of a t-bone-shaped naphthalimide derivative [2-(2-aminoethyl)-1H-benzo[de]isoquinoline-1,3(2H)dione] (NAP), which gives rise to a photoinduced electron transfer (PET) mechanism, has been established using a combination of experimental and theoretical studies. In parallel an in vitro-in cell PET mechanism has also been shown. To understand the photophysics of NAP, solvent studies have been carried out in different solvents. In addition, theoretical calculations have been conducted to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…36 Similarly, Singharoy et al, and Yang et al, with the help of naphthalimide as precursor, have demonstrated the combinational logic gate behaviour along with their different applications. 37,38 In view of the competitive advantages mentioned above, we have demonstrated a uorescence switching phenomenon of NDI probes in response to the external stimuli and realized their behaviour in binary format to implement in digital logic gates. The novelty of the presented work lies in achieving the modulation of uorescent ON/OFF switching using NDI congeners concerning the use of external stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Similarly, Singharoy et al, and Yang et al, with the help of naphthalimide as precursor, have demonstrated the combinational logic gate behaviour along with their different applications. 37,38 In view of the competitive advantages mentioned above, we have demonstrated a uorescence switching phenomenon of NDI probes in response to the external stimuli and realized their behaviour in binary format to implement in digital logic gates. The novelty of the presented work lies in achieving the modulation of uorescent ON/OFF switching using NDI congeners concerning the use of external stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…36 Similarly, Singharoy et al , and Yang et al , with the help of naphthalimide as precursor, have demonstrated the combinational logic gate behaviour along with their different applications. 37,38 …”
Section: Introductionmentioning
confidence: 99%
“…To get better results, we optimized the ground and excited state geometries of ANHP by DFT/6‐311G and CIS/6‐311G methods, respectively. We then calculated the absorption and emission spectra of ANHP using the TD‐DFT method with the B3LYP exchange‐correlation functional. The results of theoretical calculations corresponded to the experimental observations.…”
Section: Methodsmentioning
confidence: 99%
“…For The results of stationary fluorescence and fluorescence kinetics analysis are shown in Figure 5 and Figure S4. Fluorescence kinetics (Figure S4) analysis allowed for the calculation of the contribution of an exponent with a characteristic time of 6.0 ns corresponding to free naphthalimide−which was 52% (calculated from the known values 36 of the pre-exponential factors = 619 /(619 + 561) = 0.52), i.e. there is an increase in contribution of this component if compared to neutral pH, where it was 37%.…”
Section: Bioconjugate Chemistrymentioning
confidence: 99%